Development of Comic-Based Arabic Learning Media to Increase Vocational Students’ Learning Motivation - Rina Dian Rahmawati; Muhamad Sulthon Sholahudin; Siti Indatul Lailiyah; Mohammad Zakiyuddin; Faisal Mahmoud Adam Ibrahim (Izdihar : Journal of Arabic Language Teaching, Linguistics, and Literature, 2025)
This study aimed to develop comic-based learning media for Arabic language instruction in Class X Culinary Arts at Hasbullah Bahrul Ulum creative Vocational School in Tambakberas Jombang. This research used a development approach with the ADDIE model (Analyze, Design, Develop, Implement, Evaluate). The data used were both quantitative and qualitative, collected through observation, interviews, questionnaires, pre-tests, post-tests, and documentation. Data analysis was conducted using descriptive statistics and a paired sample t-test. The validation results indicated that the developed comic-based learning media is highly valid and effective in increasing students' learning motivation, with a media expert validation score of 95% (very valid category) and a material expert validation score of 93.3% (very valid category). The novelty of this research lied in the application of comic-based media in Arabic language learning for vocational school students, which has been rarely explored in previous studies. This media emphasizes not only the language learning aspect but also the enhancement of students' motivation and engagement, which are key factors in achieving learning outcomes.